A surveillance study of the current status of reirradiation and patterns of practice. (23rd January 2017) - Yamazaki, Hideya; Fushiki, Masato; Mizowaki, Takashi; ,
Abstract: The aim of this study was to survey the current status of reirradiation (Re-RT) and patterns of practice in Japan. An email questionnaire was sent to Kansai Cancer Therapist Group partner institutions, using questions similar to those in the Canadian radiation oncologist (RO) survey (2008). A total of 34 ROs from 28 institutions returned the survey. All 28 institutions experienced Re-RT cases in 2014. However, 26 of the 28 institutions (93%) reported difficulty in obtaining Re-RT case information from their respective databases. Responses from 19 institutions included the number of Re-RT cases; this rose from 183 in the period 2005–2009 (institution median = 4; 2–12.9) to 562 in the period 2010–2014 (institution median = 26; 2–225). Important considerations for indication of Re-RT were age (65%), performance status (83%), life expectancy (70%), absence of distant metastases (67%), and interval since previous treatment (73%). Previous total radiation dose (48%), volume of tissue irradiated (72%), and the biologically equivalent dose (BED; 68.5%) were taken into account during Re-RT planning. These factors were similar to those considered in the Canadian survey; however, the present study did not consider age. In eight site-specific scenarios, barring central nervous system recurrence, more than 90% of ROs agreed to perform Re-RT, which was higher than the percentage observed in the Canadian survey. Re-RT cases have increased in number and aroused interest among ROs in this decade of advanced technology. However, consensus building to establish guidelines for the practice and prospective evaluation of Re-RT is required.